The Implementation of Non-Smoking Area Qanun (Regulation) in West Aceh Health Office - Veni Nella Syahputri; Fitriani Fitriani; Teungku Nih Farisni; Yarmaliza Yarmaliza; Fitrah Reynaldi; Darmawi Darmawi (Universitas Teuku Umar, 2019)
West Aceh Regency Regulation (Qanun in Indonesia) Number 14 of 2015 concerning on Non-Smoking Areas is a regional regulation that regulates non-smoking areas in West Aceh Regency with the aim of protecting public health from the dangers caused by cigarette smoke. The purpose of this study was to determine the implementation of the Edwar III Model on aspects of communication clarity, aspects of authority, aspects of disposition or attitude, and aspects of Standard Operating Procedures (SOP) in implementing Non-Smoking Area Qanun in the West Aceh Health Office. The methodology used in this study is qualitative research in which the data collection is done by interviewing selected informants by purposive sampling, namely 2 (two) main informants and 5 (five) triangulation informants. The results of this study showed that: in the aspects of communication-the head office has provided the information about Non-Smoking Area Regulation (Qanun). The aspect of authority: the implementation of regulation is determined as head office authority. The attitude aspects: employees still have an attitude that incompliant with the implementation of the Non-Smoking Area Regulation (Qanun). The Standard Operating Procedures (SOP) aspect is that the Health Office does not have an SOP yet to regulate the Health Office internally in implementing the Non-Smoking Area Regulation (Qanun). The conclusion of this study is that the implementation of Non-Smoking Areas Regulation (Qanun) in the Health Office is still not comprehensively implemented due to the absence of guidance, supervision and punishments for violators of Non-Smoking Area Regulation (Qanun). Therefore, it is recommended that head office be able to implement supervisors, supervision, and punishments to violators of Non-Smoking Areas Regulation (Qanun) thus the healthy circumstance can be created in working area.